2020
DOI: 10.1038/s41467-020-20091-6
|View full text |Cite|
|
Sign up to set email alerts
|

Small molecule inhibition of Dynamin-dependent endocytosis targets multiple niche signals and impairs leukemia stem cells

Abstract: Intensive chemotherapy for acute leukemia can usually induce complete remission, but fails in many patients to eradicate the leukemia stem cells responsible for relapse. There is accumulating evidence that these relapse-inducing cells are maintained and protected by signals provided by the microenvironment. Thus, inhibition of niche signals is a proposed strategy to target leukemia stem cells but this requires knowledge of the critical signals and may be subject to compensatory mechanisms. Signals from the nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 98 publications
1
26
0
Order By: Relevance
“…This points to the involvement of also other endocytosis-related, or non-related, mechanisms in the induction of the cell death response. In line with this, it has recently been suggested that dynamin inhibition blocks ligand-bound receptor internalization in leukemia cells, leading to apoptosis [ 16 ].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This points to the involvement of also other endocytosis-related, or non-related, mechanisms in the induction of the cell death response. In line with this, it has recently been suggested that dynamin inhibition blocks ligand-bound receptor internalization in leukemia cells, leading to apoptosis [ 16 ].…”
Section: Discussionmentioning
confidence: 89%
“…Hence, we favor the notion that dynamin inhibition preferentially impacts on proliferating cells. Notably though, previous investigations have suggested that dynamin inhibition can have an impact on cells with both low and high proliferative capacity [ 16 ]. Nevertheless, we here provide data on the effect of dynamin inhibition on non-adherent cancer cells, which complements previous studies where the focus has predominantly been on adherent cell lines [ 12 , 13 , 24 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prostate cancer mouse model in which formation of subcutaneous tumors are induced after injection of human prostatic adenocarcinoma cells, intratumoral injection of a DNM2 inhibitor (N'- [4-(dipropylamino) benzylidene]-2-hydroxybenzohydrazide, DBHA) rapidly reduces tumor size without apparent adverse effect [89]. In the same line, continuous delivery of the CyDyn4-36 DNM2 inhibitor by subcutaneous osmotic pumps reduces the size of established tumors formed by prior intracranial injection of glioma stem cells [82] and intraperitoneal injection of the Dynole 34.2 DNM2 inhibitor leads to progressive exhaustion of pre-leukemia stem cells in a mouse model of acute leukemia [90]. Dynole 34.2 also reduces the number of leukemic cells in the bone marrow and spleen of mice after T-ALL and acute myeloid leukemia cells xenografts [90].…”
Section: Therapeutic Developmentsmentioning
confidence: 99%
“…In the same line, continuous delivery of the CyDyn4-36 DNM2 inhibitor by subcutaneous osmotic pumps reduces the size of established tumors formed by prior intracranial injection of glioma stem cells [82] and intraperitoneal injection of the Dynole 34.2 DNM2 inhibitor leads to progressive exhaustion of pre-leukemia stem cells in a mouse model of acute leukemia [90]. Dynole 34.2 also reduces the number of leukemic cells in the bone marrow and spleen of mice after T-ALL and acute myeloid leukemia cells xenografts [90]. DBHA, Dynole 34.2 and CyDyn4-36 represent a new generation of DNM2 inhibitors opening the way for future clinical use.…”
Section: Therapeutic Developmentsmentioning
confidence: 99%